What question are you needed answers to?
Answer:
(x-7) (x-8)
Step-by-step explanation:
Break the expression into groups:
= x(x-7) -8(x-7)
Factor out x from:
x^2-7x x(x-7)
Factor out -8 from -8x+56:
-8(x-7)
=x\left(x-7\right)-8\left(x-7\right)
The solution of the given equation 4(3x - 4) - 7( 2x + 3) = 3 is -20.
<h3>What is a linear equation?</h3>
A linear equation is an equation that has the variable of the highest power of 1.
The standard form of a linear equation is of the form Ax + B = 0.
The given equation is;
4(3x - 4) - 7( 2x + 3) = 3
To solve;
4(3x - 4) - 7( 2x + 3) = 3
Solve the parentheses using the distributive property;
12x - 16 - 14x - 21 = 3
we need to get the like terms together;
12x - 14x -16 - 21 = 3
-2x - 37 = 3
Add 37 both sides, we get;
-2x = 40
Divide both sides by -2
x = -20
Hence, the solution of the given equation is -20.
Learn more about linear equations;
brainly.com/question/10413253
#SPJ1
Each piece of cake costs $.56 ($.55875)
I divided 8.94 by 16 to find how much one piece costs.